2010
DOI: 10.1057/jt.2010.15
|View full text |Cite
|
Sign up to set email alerts
|

The chain of effects from reputation and brand personality congruence to brand loyalty: The role of brand identification

Abstract: Very few previous studies have looked at brand identification, which is surprising considering it is such an important variable to influence brand loyalty. This study investigates the influences of brand personality congruence and reputation on brand identification and loyal behaviour. A theoretical model is proposed and evaluated with a sample of car owners in Germany. It was found that brand personality congruence and reputation affect brand identification, which in turn impacts on brand loyalty. Furthermore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
93
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(101 citation statements)
references
References 59 publications
6
93
0
2
Order By: Relevance
“…On the side of brand loyalty, it was considered a key marketing concept and extensively researched for an understanding of its significant importance in developing brand trust, brand equity, image and awareness (Han & Jeong, 2013;Wirtz, Den Ambtman, Bloemer, Horváth, Ramaseshan, Van de Klundert, 2013;He & Li, 2011;Kuenzel & Halliday, 2010;Ryu, Han & Kim, 2008).…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…On the side of brand loyalty, it was considered a key marketing concept and extensively researched for an understanding of its significant importance in developing brand trust, brand equity, image and awareness (Han & Jeong, 2013;Wirtz, Den Ambtman, Bloemer, Horváth, Ramaseshan, Van de Klundert, 2013;He & Li, 2011;Kuenzel & Halliday, 2010;Ryu, Han & Kim, 2008).…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…Finally, virtual communities consist of individuals who have common interests and goals. Future research may want to examine whether the value congruity of consumer-consumer (Shen, Huang, Chu, & Liao, 2010) and consumer-brand (Kuenzel & Halliday, 2010) will moderate the effects observed in the present research. Investigating these issues will further advance our understanding of eWOM intentions in SNSs.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 97%
“…Kuenzel and Halliday (2008) confirm that brand prestige positively affects consumers' brand identification. Also, Kuenzel and Halliday (2010) address that consumers have a higher level of brand identification when they perceive a reputable brand. Moreover, Lii and Lee (2012) testing CSR reputation (prestige) as a moderator of the relationship among CSR initiatives, consumer-company identification, and brand attitude, found that CSR initiatives have a significant effect on consumer-company identification and brand attitude.…”
Section: Literature Reviewmentioning
confidence: 99%